Microbial induced calcite precipitation treatment on tropical residual soil - Tiong, Kenny Ping Chiet (2016)
Biomediated soil improvement, also known as Microbial Induced Calcite Precipitation (MICP), is a promising new branch of microbial geotechnology. Earlier MICP studies only focused on sandy soils, but more recent studies have also investigated the potential and feasibility of MICP on tropical residual soil. The main objective of this study is to examine the feasibility of MICP and the mechanisms involved between two types of bacteria and chemical reagents in improving the strength of tropical residual soil. Essentially, this was about identifying the optimized treatment conditions as well as the effects of some specific MICP parameters and curing on unconfined compressive strength (UCS) development and calcite distribution. Two bacteria from the Bacillus family, namely, Bacillus subtilis and Sporosarcina pasteurii, were used as urease producing bacteria. The tropical residual silt soil with 80% fine soil was compressed to a cylindrical sample measuring 100 mm in height and 50 mm in diameter as well as having a dry density of 1.31 Mg/m3. Continuous injection method was employed. Series of tests were carried out, with each having different chemical reagents concentrations (0.15, 0.25, 0.35 or 0.45 M), reagent flow pressures (0.1, 0.2, 0.3 or 0.4 bars), and treatment durations (24, 48, 72 or 96 hours). Strength improvement of about 56.70% and 38.14% was immediately discovered after MICP treatment using Sporosarcina pasteurii and Bacillus subtilis, respectively. Additionally, strength improvement of about 30 to 104.12% were recorded after curing the samples for 3, 7, 14, 20, and 28 days. The optimum curing period was 14 days. The optimum treatment condition of MICP treatment for both bacteria consisted of 0.25 M of reagent concentration, 0.2 bars of reagent flow pressure, and 48 hours of treatment duration. The reagent flow pressure was the only MICP parameter that affected calcite distribution. No clear correlation was observed between calcite precipitation and strength. The two bacteria had distinctive responses to the designated treatment conditions as the behaviour of living microorganisms could differ although they are from the same family. This information were analysed to establish design charts for MICP practitioner in selecting optimal MICP parameters under different circumstances.